MODIFIKASI AMONIUM OKSALAT DENGAN PEWARNA ALAMI BIT MERAH SEBAGAI FORMULA BARU REAGEN HITUNG JUMLAH TROMBOSIT - Kartika - Ikawati; Agus Widodo (LPPM Universitas Abdurrab, 2024)
Abstract Platelet count using the Brecker koncrete method with 1% Ammonium oxalate reagent has a weakness that it cannot color platelets so that they are difficult to count. Red beet contains natural dyes that can color platelet organelles. This study aims to prove the ability of Ammonium oxalate modification with natural red beet dye (Beta vulgaris L) as a new formula for platelet count reagents. Method. This type of research is a laboratory experiment with a comparison of platelet counts using 1% Ammonium oxalate reagent and modification of Ammonium oxalate-red beet extract in a ratio of 1: 1, 1: 2, 2: 1 and automatic methods. The object of research is EDTA venous blood from 30 samples of AAK 17 Semarang students taken using the convenience sampling technique. Manual platelet counts using the Brecker concrete method with a counting chamber and an automatic method using a hematology analyzer. The sharpness of platelet staining is assessed under a microscope. The comparison test uses Repeated Anova. The results of the study showed that the color of platelets examined with the Ammonium-bit modification reagent (1: 2) was sharper with an average number approaching the gold standard. The statistical test results obtained sig 0.069 (> 0.05) or no significant difference. Beet extract (Beta vulgaris L) has the potential as an alternative natural dye in manual platelet counts (Brecer koncrite) keywords : trombosit, red bit, Amonium oksalat